Type 1 diabetes through two lenses: comparing adolescent and parental perspectives with photovoice. (December 2016) - Walker, Ashby; Schatz, Desmond; Johnson, Cathryn; Silverstein, Janet; Lyles, Shannon; Rohrs, Henry
Abstract Background Parental support and care-coordination are vital for youth with type 1 diabetes (T1D) in achieving positive health outcomes. Yet, studies are rarely designed to identify factors that influence parent/youth collaboration or how their perspectives about diabetes may vary. Methods Photovoice was used to explore how adolescent and parental perspectives on T1D compare to identify factors that may influence care collaboration. A follow-up study was conducted where parents/caregivers of adolescents with T1D were prompted to take and explain five photos capturing what diabetes meant to them. Selection criteria included having a child 12–19 years with a diagnosis of T1D (≥2 years since onset). Thirty-three parents/caregivers participated (24 mothers, six fathers, two grandmothers, and one grandfather of 19 sons/14 daughters; mean age 15 years [±2.1]; mean disease duration 6 years [±3.3]). Content analysis was used to compare parent/caregiver photos with those captured by adolescents in a previous study with 40 youth participants (20 males/20 females; mean age 15 years [±1.9]; mean disease duration 6 years [±3.9]) through a method of constant comparison. Socioeconomic status was measured by household income and parental education. Glycemic control was captured by HbA1c. Mann-Whitney U testing was used to compare representations across demographic variables (202 youth photos, 153 parental photos). Results Over half of adolescents and parents took at least one photo of: (1) diabetes supplies (2) food (3) coping mechanisms/resilience and (4) disease encroachment. Parents and adolescents similarly framed food-related issues as a major source of frustration in diabetes care. However, narratives about diabetes supplies differed: adolescents framed supplies as a negative aspect of diabetes whereas parents tended to celebrate supplies as improving life. Also, images of disease encroachment differed: adolescents took photos of their bodies to depict how diabetes trespasses on their lives whereas parents took pictures of clocks to denote sleep disruption or exhaustion from constant care demands. Conclusions Food-related issues and varying views on supplies may trigger diabetes-specific conflicts. Contrasting viewpoints about the most cumbersome aspects of diabetes may provide insight into differential paths for interventions aimed at offsetting the burdens of T1D for adolescents and parents.